Cotton textile industry in Zambia: The economic viability of revamping Mulungushi Textiles Limited - Munoni, Chiluba Mercy (Graduate School of Development Policy and Practice, 2017)
The agriculture and manufacturing sectors have been identified and prioritized by the Zambian government as sectors that could contribute significantly to poverty reduction through industrialization and creation of employment. The cotton textile industry is one such industry that cuts across the two sectors. This research paper focuses on the cotton textile industry in Zambia, with specific emphasis on Mulungushi Textiles Limited that was reopened by the Republican President, His Excellency, Mr. Edgar Chagwa Lungu in August 2016 after having been closed for about a decade. To this end, the main objective of the research paper is to analyze the economic viability of revamping Mulungushi Textiles Limited by focusing on determinants of viability which included; production cost, government policies and strategies, and institutional arrangements, among others. The study analyzes mainly qualitatively both primary and secondary data. Primary data was principally sourced through interviews and observations, while secondary data was through online and physical sources such as books, reports and other written publications. From the research findings, Mulungushi Textiles Limited factory machinery is obsolete and dilapidated to fully operationalize the business strategic units of ginning, spinning, weaving, dyeing and printing, garment production and cooking oil processing. The study recommends that the factory should undergo a complete overhaul in the long run and in the short run, resume garment production which was identified to be a low hanging fruit. The study concludes that, with the right investment, policies, strategies and concerted efforts from both the public and private sectors, revamping Mulungushi Textiles Limited is economically viable and has great potential to contribute to the government's efforts in promoting inclusive growth through poverty reduction, particularly in rural areas where poverty is mostly prevalent.